2022
DOI: 10.3390/min12020211
|View full text |Cite
|
Sign up to set email alerts
|

A Joint Experiment and Discussion for Strength Characteristics of Cemented Paste Backfill Considering Curing Conditions

Abstract: As lots of underground mines have been exploited in the past decades, many stope instability and surface subsidence problems are appeared in the underground mines, while the cemented paste backfill (CPB) technology has been applied for more than 40 years, and it can solve these problems. As it is shown that the effect of backfilling is mainly affected by the mechanical properties of the CPB, and there are lots of factors which can influence the strength of the CPB, but the coupled effects of curing conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Studies [ 37 , 38 , 39 ] have shown that under the condition of positive-temperature curing, the strength of CTB comes from the interaction force between the cementation force of hydration products such as C-S-H gel, Aft, and CH on tailings particles. Under the action of continuous load, the micropores and microcracks in CTB are closed, and the aggregate particles and cementation bodies (the hydration products and aggregate particles are cemented) become denser.…”
Section: Discussionmentioning
confidence: 99%
“…Studies [ 37 , 38 , 39 ] have shown that under the condition of positive-temperature curing, the strength of CTB comes from the interaction force between the cementation force of hydration products such as C-S-H gel, Aft, and CH on tailings particles. Under the action of continuous load, the micropores and microcracks in CTB are closed, and the aggregate particles and cementation bodies (the hydration products and aggregate particles are cemented) become denser.…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al [ 11 ] found that sulfur content enhances early strength but inhibits later compressive strength. Chen et al [ 12 ] propose that tailing sulfide adversely affects the setting time and compressive strength of backfill. Ercikdi et al [ 13 ] conducted compressive strength tests on backfill after desulfurization of tailings and concluded that the strength of desulfurized backfill significantly improves.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the backfilling mixture in the flow phase has had enough attention devoted to it in works [34,35]. The strength characteristics of the artificial rock are highlighted in works [36]. The composition of the backfilling mixture is selected in such a way as to resist the action of mining pressure, to prevent the appreciable deformation of the Earth's surface in underground mining operations [37,38].…”
Section: Introductionmentioning
confidence: 99%